Uterine Rupture with Cesarean Scar Heterotopic Pregnancy with Survival of the Intrauterine Twin - Kimberly R. Lincenberg; Eric R. Behrman; James S. Bembry; Christine M. Kovac (Hindawi Limited, 2016)
Background. Heterotopic pregnancy is a multiple gestation with both intrauterine and ectopic fetuses. A cesarean scar ectopic pregnancy is when the fetus has implanted over the previous hysterotomy site. A known complication of cesarean scar ectopic pregnancy is uterine rupture, which can cause great morbidity and mortality. Case. 28-year-old G5P3105 at 10 weeks with a dichorionic diamniotic gestation was found to have a ruptured uterus with expulsion of a cesarean scar ectopic pregnancy and retention of the intrauterine fetus. After uterine repair, the singleton gestation reached viability was delivered by emergent cesarean section for placental abruption. Conclusion. Safe management of cesarean ectopic pregnancy requires early diagnosis by ultrasonography. With early detection, management can focus on preventing maternal morbidity of uterine rupture and life-threatening hemorrhage.